2019
DOI: 10.1038/s41598-019-50680-5
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide Age at Onset of Female Breast Cancer: A 25-Year Population-Based Cancer Registry Study

Abstract: A higher frequency of early onset female breast cancers (BC) has been observed in low/middle income countries than in high income countries. We quantified the role of population ageing to this pattern using data from all population-based cancer registries (CRs) worldwide. Patients’ median age at BC onset and that of the general population were extracted for CRs listed in volumes VI (1983–1987 years) through XI (2008–2012 years) of Cancer Incidence in Five Continents. Their association was assessed at cross-sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 23 publications
3
41
1
1
Order By: Relevance
“…Breast cancer onset is proportional to the median age of the underlying population at risk. 14 In this prospective study, the material median age at breast cancer diagnosis was 58.0 years, in line with most reports from Western countries with mammography screenings. 15 16 It has been reported that both young and old age at breast cancer onset indicates a poorer prognosis, compared with 'middle-aged' women, 17 18 although this observation has not been present unanimously in all studies.…”
Section: Discussionsupporting
confidence: 87%
“…Breast cancer onset is proportional to the median age of the underlying population at risk. 14 In this prospective study, the material median age at breast cancer diagnosis was 58.0 years, in line with most reports from Western countries with mammography screenings. 15 16 It has been reported that both young and old age at breast cancer onset indicates a poorer prognosis, compared with 'middle-aged' women, 17 18 although this observation has not been present unanimously in all studies.…”
Section: Discussionsupporting
confidence: 87%
“…The difference can be associated with geographical and ethic variations. It has been reported that the mean age of patients at diagnosis of breast cancer in Asian populations is lower than that in Western populations ( 27 29 ). A large series of mucinous cancer study in Korea also revealed that the mean age of the patients was younger than those of previous reports ( 30 ).…”
Section: Discussionmentioning
confidence: 96%
“…In this large multicenter study, a pathological finding was detected in 0.8% of patients during workup of the RM specimen, including 0.2% patients with occult invasive breast cancer, confirming a low incidence of breast cancer detected during RM. Older patients were more likely to have a diagnosis of incidentally found breast cancer, though their median age (51 years) was lower than that of the overall breast cancer population (median~62 years), which is explained by the younger age structure of the study sample [10].…”
Section: Discussionmentioning
confidence: 72%